A prediction scheme of mobility of cognitive femtocells LTE-A / LTE-UE under different speed scenarios - Vara Prasad Padyala, Venkata; K.V.D.Kiran, Dr (International Journal of Engineering and Technology, 2018)
Cognitive Femtocells have been standardized suitably to the technical framing of the Fourth cohort compact project to place them inside and outside the cell. Cognitive femtocells expand the coverage area and meet the future demands of higher data rates. However, as a result of the massive deployment of cognitive femtocells, users experience additional delay and unnecessary deliveries. The different hand off mechanisms are 1. Hard handover (break before make) 2. Smooth or soft handover (make-before-break). This can seriously affect the quality of service (QoS) of jam sensitive applications, such as Voice over long-term evolution (VoLTE). The 4GPP LTE-A / LTE-UE wireless networks aim to provide uninterrupted movement and rapid transfer pillar for (Real Time) RT and non-RT application services under the giant vigour. The prediction of mobility is an effective technique to identify a domestic NodeB (eNB / HeNB) evolved in the future and improve the overall service quality of the network and satisfy the end user experience. The different hand over mechanisms are, the first sense of a difficult delivery or transfer is one in which an breathe link should be penetrate ahead a unused one is created. The second new 3G technologies use CDMA where it is possible to have adjoining cells at the same frequency and this opens the odds of boast a transfer or transfer from where it is not required to repair the connection. This is called soft transfer, and is defined as a handover in which a not used tie-in is established before the used one is released. The third type of delivery is called smoother delivery or transfer. In this case, a pristine signal is added or deleted from the spry signal group. It can also happen when a signal is replaced by a burly signal from another sector under the base station. This type of transfer is available within UMTS and CDMA2000. â€œThe cognitive femtocell will do in the delivery mechanism is that it will detect the new channel to transmit the data. With this we can avoid the delivery handover mechanismâ€. This study investigates the role of mobility prediction in reducing the end-to-end delay of VoLTE and the delay of handover under different user equipment (UE) speeds in mixed femtocell and macrocell environments. We propose a mobility based forecasting scheme based on the user path and measurements of the received signal reference signal and the quality reference signal (RSRP / RSRQ) with mixed RT traffic and not RT and then estimated using a network model new. The survey analysis shows that the proposed scheme will reduce the delivery delay by 35% to keep VoLTE at the end of the delay.Â Â
Keywords: Cognitive Femtocell; Handoff/ Handover; LTE; LTE-A; LTE_UE; Femtocell; Macrocell; VoLTE..